Acute hemorrhagic necrotizing enterocolitis caused by non-O1/non-O139 Vibrio cholerae infection: A case report. Issue 25 (25th June 2021) - Wu, Mingjie; Zhou, Liangjing; Cao, Liping
Abstract: Rationale: Acute hemorrhagic necrotizing enterocolitis (AHNE) is a rapidly progressive and extremely dangerous disease. Here we report a rare case caused by Vibrio cholerae ( V cholerae ). Patient concerns: A 70-year-old man was admitted to our emergency department because of a sudden loss of consciousness. Diagnoses: On admission with severe toxic shock, the patient presented with elevated body temperature, decreased blood pressure, abdominal tenderness and rebound pain, predominantly on the right side. Computed tomography showed swelling and thickening of the right colon and peritoneal effusion. Necrosis was found in the hepatic flexure of the colon. On the basis of these results, the patient was diagnosed with AHNE. Interventions and outcomes: After fluid resuscitation, an exploratory laparotomy was performed immediately. The procedure was successful. Despite antibiotic therapy, the patient's clinical condition progressively deteriorated and he died of multi-organ failure on day 3 after admission. Lessons: AHNE is a rapidly progressive and extremely dangerous disease. Here we report a case of AHNE caused by non-O1/non-O139 V cholerae infection. The clinical features, phenotypic analyses and the presence of a panel of known virulence genes in the isolated strain are described. To the best of our knowledge, this is the first report of V cholerae causing severe AHNE, which is of profound pedagogical significance.